Online Attendance System Website-Based at The Village Hall Office Paya Bakung Using The Waterfall Method - Ramadani, Silvia Sindi; Kurniawan, Heri; Wijaya, Rian Farta (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Attendance is a system for recording employee attendance which is carried out in every agency, including government agencies. The Paya Bakung Village Hall Office still applies a manual attendance system so that the recording of employee attendance activities is still relatively minimal. Performing the attendance process manually takes a long time to record incoming hours, outgoing hours, or recap employee attendance reports. From these problems, the author designs and builds a computerized attendance system that can record all attendance activities of employees. Each employee has their own account that can be accessed through the employee’s device. Employees can do absent entry and absence every day. The admin records all absent data entered by employees. The web-based attendance system in this study was created using the waterfall method consisting of Requirement Analysis, System and Software Design, Implementation and Unit Testing, Operation and Maintenance. This attendance system provides great benefits for the Paya Bakung Village Hall Office